Ekplorasi Senyawa Ekstrak Etanol Rumput Belulang (Eleusine indica (L.) Gaertn) Menggunakan LC-MS/MS-QTOF Serta Uji Aktivitas Anti-Diare: In-Vivo - Pratama, Rizki Rahmadi; Septianto, Andre; Al-Hasyimi, Said Muhammad; Herliana, Herliana; Hasniah, Hasniah; Muslikh, Faisal Akhmal (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Diarrhea is one of the diseases caused by symptoms of intestinal tract infections due to various microorganisms. Goosegrass (Eleusine indica (L.) Gaertn) is a wild weed that has long been used as a traditional medicine, attributed to its phytochemical compounds such as tannins, alkaloids, flavonoids. This study aims to evaluate the antidiarrheal effects of Eleusine indica extract by comparing six treatment groups: a healthy group, a negative control group (Na-CMC), a positive control group (Loperamide 2 mg), and three variations of the extract dosage. Observations were made over 360 minutes at 30-minute intervals, using a fecal consistency scale from 1 (solid) to 5 (liquid). LC-MS/QToF analysis identified 25 secondary metabolites in the extract, including flavonoids (Schaftoside, Orientin, Vitexin, Tricin), phenolic compounds, and terpenoids. In vivo testing showed that the third dose of Eleusine indica grass extract had the most optimal antidiarrheal effect among the three doses, as evidenced by its ability to reduce diarrhea frequency, decrease fecal weight, shorten diarrhea duration, and improve fecal consistency, approaching the effectiveness of Loperamide 2 mg as a positive control. These findings suggest the potential of Eleusine indica extract as a promising natural antidiarrheal agent.